Preliminary evidence supports circulating microRNAs as prognostic biomarkers for type 2 diabetes. (27th October 2017) - Flowers, E.; Kanaya, A. M.; Fukuoka, Y.; Allen, I. E.; Cooper, B.; Aouizerat, B. E.
Summary: Background: Circulating microRNAs are emerging as potential prognostic biomarkers for the development of type 2 diabetes. However, microRNAs are also associated with complications from impaired glucose metabolism (e.g. endothelial cell function). Prior studies have not evaluated for associations between trajectories of circulating microRNAs with trajectories of fasting blood glucose over time and the responses to behavioral interventions to reduce risk. This study performed longitudinal assessment of microRNAs and fasting blood glucose and identified relationships between microRNAs and behavioral risk reduction interventions. Methods: MicroRNAs ( n = 353) were measured in subsets ( n = 10, n = 8) of participants from previously completed clinical trials that studied behavioral risk reduction interventions. Fasting blood glucose trajectories were associated with changes in 45 microRNAs over 12 months. Results: Following a 3‐month physical activity and dietary intervention compared with baseline, 13 microRNAs were differentially expressed. Seven microRNAs (i.e. miR‐106b, miR‐20b, miR‐363, miR‐486, miR‐532, miR‐92a and miR‐93) were commonly identified between the two analyses. Conclusions: Further studies are needed to determine which microRNAs are prognostic biomarkers of risk for type 2 diabetes versus consequences of impaired glucose metabolism. Additional future directions of this research are to differentiate whether microRNAs are prognostic and/or diagnostic biomarkers for risk for type 2 diabetes and predictive biomarkers of responses to risk reduction interventions.